2022
DOI: 10.3389/fcvm.2022.945142
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial dysfunction in heart failure and its therapeutic implications

Abstract: The ATP consumption in heart is very intensive to support muscle contraction and relaxation. Mitochondrion is the power plant of the cell. Mitochondrial dysfunction has long been believed as the primary mechanism responsible for the inability of energy generation and utilization in heart failure. In addition, emerging evidence has demonstrated that mitochondrial dysfunction also contributes to calcium dysregulation, oxidative stress, proteotoxic insults and cardiomyocyte death. These elements interact with eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 139 publications
1
11
0
Order By: Relevance
“…These results strongly suggest that CSE causes mitochondrial dysfunction, leading to contractile dysfunction and cardiomyocyte death as observed in Figs 1 – 3 . Similar CSE-induced mitochondrial abnormalities have been reported [ 31 ], and emerging evidence has demonstrated that mitochondrial dysfunction contributes to the contractile dysfunction of cardiomyocytes [ 32 ].…”
Section: Discussionsupporting
confidence: 73%
“…These results strongly suggest that CSE causes mitochondrial dysfunction, leading to contractile dysfunction and cardiomyocyte death as observed in Figs 1 – 3 . Similar CSE-induced mitochondrial abnormalities have been reported [ 31 ], and emerging evidence has demonstrated that mitochondrial dysfunction contributes to the contractile dysfunction of cardiomyocytes [ 32 ].…”
Section: Discussionsupporting
confidence: 73%
“…With the development of HF, myocardial fuel gradually shifts from fatty acids to glucose. [42] In addition, mitochondria-mediated cardiomyocyte apoptosis plays a significant role in the development of HF. Impaired mitochondrial structure and function can lead to cell apoptosis, myocardial metabolic remodeling, and chronic HF.…”
Section: Enhancing the Digestion And Absorption Of Lipidsmentioning
confidence: 99%
“…The nonspecific high conductance channels of mitochondrial permeability transition pore (mPTP) mediate the transition of mitochondrial permeability. Opening of mPTP leads to collapse of mitochondrial membrane potential, resulting in uncoupling of oxidative phosphorylation and ATP consumption [ 6 , 21 ]. Related studies have shown that changes in mitochondrial permeability are associated with heart failure, hemorrhagic shock, hypertension, cardiomyopathy and cardiac I/R injury [ 14 , 15 , 22 , 23 ].…”
Section: The Role Of Mitochondria In Cardiovascular Systemmentioning
confidence: 99%
“…Cardiomyocytes are one of the cell types with the highest content of mitochondria, and are highly dependent on mitochondrial oxidative phosphorylation to produce ATP. Mitochondria adapt quickly to changing environments to maintain metabolic homeostasis [ 5 , 6 ]. Mitochondria dysfunction involves in the onset and development of CVD.…”
Section: Introductionmentioning
confidence: 99%